2021
DOI: 10.47059/revistageintec.v11i3.1918
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Service Quality, Promotion Strategy and Company Image on Word of Mouth in Mediation by Online Transport Customer Satisfaction Jakarta Region

Abstract: Application-based (online) transportation is increasingly being used in the current era in fulfilling consumer needs in transportation. Apart from the convenience aspect, the company's image from online transportation is also a consideration for consumers in using these transportation services. Also, one aspect that has recently become a consideration for consumers in using online transportation is the promotional strategy that the company offers to consumers. These three aspects are important factors that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This literature review aims to provide a comprehensive overview of relevant studies conducted in the last five years, arranged in chronological order, and critically evaluated for their contributions to the field. One of the early studies by Tecoalu (2021) explored the impact of corporate image on travel intention. The study found a significant positive relationship between corporate image and travel intention, indicating that a positive perception of a travel service provider's reputation and image enhances individuals' likelihood of choosing their services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This literature review aims to provide a comprehensive overview of relevant studies conducted in the last five years, arranged in chronological order, and critically evaluated for their contributions to the field. One of the early studies by Tecoalu (2021) explored the impact of corporate image on travel intention. The study found a significant positive relationship between corporate image and travel intention, indicating that a positive perception of a travel service provider's reputation and image enhances individuals' likelihood of choosing their services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Poor service quality can also lead to negative word of mouth and damage the reputation of a travel service. In order to succeed in the tourism industry, it is important for travel services to prioritize reputation and quality, as these factors can have a significant impact on customer satisfaction and loyalty (Tecoalu, 2021). Pakistan's travel industry has been neglected in recent years, which has contributed to poor performance and low productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Sumaedi, in 2012, studied paratransit [35], and then he studied the satisfaction level public of the bus in 2016 [24] by connecting perceived value, image, perceived ease of use, and perceived passengers' satisfaction using factor analysis. Tecoalu was concerned to evaluate online transport [36]. While Supriyadi was concerned about the JAKLINGO microbus [37].…”
Section: Introductionmentioning
confidence: 99%